The German entrepreneurial index (GEX®): a primer on an ownership-based style index in Germany - Ann-Kristin Achleitner; Christoph Kaserer; Markus Ampenberger; Florian Bitsch (Technische Universität München, Center for Entrepreneurial and Financial Studies (CEFS), 2009)
Recent research indicates that the majority of listed firms in Germany (and also in many other countries around the world) have a dominant owner rather than being widely-held. Hence, owner-dominated firms comprise an important subset of listed companies. This article introduces the concept of an ownership-based style index of listed firms in Germany, the German Entrepreneurial Index (GEX®). Introduced in 2005, the GEX® represents recently listed, ownerdominated firms in the German Prime Standard. We review the theoretical foundation and the index construction of the GEX®. In addition, we provide an overview of its development and performance between index inception and end of 2008 and relate this to properties of the German financial market. Finally, we conclude with a critical outlook for the index future against the background of recent developments.
Keywords: G11; G32; G34; 330; insider ownership; style index; ownership structure; corporate governance; Klein- und Mittelunternehmen; Eigentümerstruktur; Entrepreneurship-Ansatz; Eigentümer; Corporate Governance; Aktienindex; Deutschland